2012
DOI: 10.5812/ijem.4366
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Prolactin Levels in Intellectually Disabled Patients Using Antipsychotic Medications

Abstract: BackgroundPatients with intellectual disabilities may be treated with antipsychotic medications for a variety of diagnoses. Use of this category of medication can increase prolactin levels and place the patient at risk for sexual dysfunction and lower bone mineral density. The proposed mechanism of action is affinity for the dopamine receptor. Use of bromocriptine, a dopamine receptor antagonist, was proposed to attenuate hyperprolactinemia.ObjectivesThe objectives of this study were to (1) review serum prolac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In this study, we found an increase in the mean value of the serum PRL level, with a statistically significant difference between T0 and T1 in the entire sample. This result is consistent with other studies that showed that one of the most frequent side effects of risperidone is the increase in PRL serum levels in both pediatric and adult populations ( Masi et al , 2001 ; Findling et al , 2003 ; Saito et al ., 2004 ; Anderson et al , 2007 ; Troost et al ., 2007 ; Calarge et al ., 2009 ; Jerrell et al ., 2009 ; Migliardi et al , 2009 ; Roke et al ., 2009 ; Grahovac et al ., 2010 ; Fraguas et al ., 2011 ; Inder and Castle, 2011 ; Perez-Iglesias et al ., 2012 ; Roke et al ., 2012 ; Bargiota et al , 2013 ; Lambert et al ., 2013 ; Margari and Petruzzelli et al ., 2013 ; Margari and Matera et al ., 2013 ). The differences in the mean values of serum PRL between T0 and T1, although not statistically significant, were higher in female patients, those in the pubertal/postpubertal stage, and risperidone dosage up to 1 mg/day, confirming previous literature data that have reported similar results ( Duval et al ., 2008 ; Johnsen et al ., 2008 ; Lambert et al ., 2013 ; Ajmal et al ., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found an increase in the mean value of the serum PRL level, with a statistically significant difference between T0 and T1 in the entire sample. This result is consistent with other studies that showed that one of the most frequent side effects of risperidone is the increase in PRL serum levels in both pediatric and adult populations ( Masi et al , 2001 ; Findling et al , 2003 ; Saito et al ., 2004 ; Anderson et al , 2007 ; Troost et al ., 2007 ; Calarge et al ., 2009 ; Jerrell et al ., 2009 ; Migliardi et al , 2009 ; Roke et al ., 2009 ; Grahovac et al ., 2010 ; Fraguas et al ., 2011 ; Inder and Castle, 2011 ; Perez-Iglesias et al ., 2012 ; Roke et al ., 2012 ; Bargiota et al , 2013 ; Lambert et al ., 2013 ; Margari and Petruzzelli et al ., 2013 ; Margari and Matera et al ., 2013 ). The differences in the mean values of serum PRL between T0 and T1, although not statistically significant, were higher in female patients, those in the pubertal/postpubertal stage, and risperidone dosage up to 1 mg/day, confirming previous literature data that have reported similar results ( Duval et al ., 2008 ; Johnsen et al ., 2008 ; Lambert et al ., 2013 ; Ajmal et al ., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on antipsychotic-induced serum PRL level variations were carried out especially on adult samples ( Grahovac et al , 2010 ; Inder and Castle, 2011 ; Perez-Iglesias et al ., 2012 ; Bargiota et al , 2013 ; Lambert et al ., 2013 ), whereas fewer data are available in children and adolescents. Studies that evaluated variations in PRL levels during treatment with risperidone reported an increase in serum levels in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Another observation about this prolactin result is that the level of prolactin in males is significantly reduced to what was observed in their female counterparts suggesting that prolactin hormone responsible for lactation in female is more relevant in females than males. This result is buttressed by the findings of Lambert et al, 2013 who found out that gender factor is a significant predictor of prolactin levels. The observed significant increases (p<0.01)in the levels of cholesterol in Alloxan-induced diabetic male and female Wistar rats, is an indication that diabetes is accompanied in most cases by hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 88%
“…When used in the management of problem behaviors or irritable mood without a clear psychotic or mood disorder diagnosis, antipsychotic therapy should reevaluated periodically, with ongoing consideration for dose tapering or medication withdrawal. 66 Tardive dyskinesia, 67 metabolic syndrome, 64 and prolactin elevation 68 are all exacerbated by prolonged duration of antipsychotic exposure. Although tardive dyskinesia can be irreversible, there can be substantial reversal of hyperprolactinemia and metabolic syndrome with the discontinuation of antipsychotic treatment.…”
Section: Risk/benefit Considerations In Drug Treatment Selectionmentioning
confidence: 99%